2016
DOI: 10.1098/rsbl.2016.0542
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic lineages hybridize for worker production in the harvester ant Messor barbarus

Abstract: The reproductive division of labour between queen and worker castes in social insects is a defining characteristic of eusociality and a classic example of phenotypic plasticity. Whether social insect larvae develop into queens or workers has long been thought to be determined by environmental cues, i.e. larvae are developmentally totipotent. Contrary to this paradigm, several recent studies have revealed that caste is determined by genotype in some ant species, but whether this is restricted to just a few exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
(36 reference statements)
0
18
0
Order By: Relevance
“…In hybridogenetic species of the ant genera Messor and Pogonomyrmex , queens are produced exclusively by intralineage sexual reproduction (Helms Cahan & Keller, ; Norman et al, ; Romiguier et al, ). Here, we showed that, in contrast, social hybridogenesis in Cataglyphis is strongly associated with queen parthenogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In hybridogenetic species of the ant genera Messor and Pogonomyrmex , queens are produced exclusively by intralineage sexual reproduction (Helms Cahan & Keller, ; Norman et al, ; Romiguier et al, ). Here, we showed that, in contrast, social hybridogenesis in Cataglyphis is strongly associated with queen parthenogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Several ant species have independently evolved such a mode of reproduction, called “social hybridogenesis”. To date, social hybridogenesis has been reported in four ant genera; in two genera where queens arise from mating between same lineage partners, hereafter called “sexual social hybridogenesis”; Messor (Norman, Darras, Tranter, Aron, & Hughes, ; Romiguier, Fournier, Yek, & Keller, ) and Pogonomyrmex (Helms Cahan & Keller, ; Schwander, Helms Cahan, & Keller, ; Sirviö, Pamilo, Johnson, Page, & Gadau, ), in one genus where queens arise from thelytokous parthenogenesis called “clonal social hybridogenesis”; Cataglyphis (Eyer, Leniaud, Darras, & Aron, ; Leniaud, Darras, Boulay, & Aron, ), and in one genus where both sexual and clonal social hybridogenesis have been documented; Solenopsis (Helms Cahan & Vinson, ; Lacy et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This study by Romiguier et al ., using RNA sequencing, and the recent study by Norman et al . (), now demonstrate a dependent‐lineage mating system in a second genus of seed‐eating ants. An intriguing feature of the dependent‐lineage system in Pogonomyrmex harvester ants is that the ratio of colonies of the two lineages (colonies with a founding queen of a particular lineage) tends to be strongly asymmetrical.…”
mentioning
confidence: 71%
“…But this may be a coincidence. It appears that two-lineage systems are widespread among the more than 14 000 species and about 20 subfamilies of ants (Norman et al 2016). It seems likely that the more we look for these systems in other genera and subfamilies, the more we will find them.…”
mentioning
confidence: 99%
“…Females of social Hymenoptera (ants, social bees and wasps) usually develop into either reproductive queens or nonreproductive workers depending on environmental factors or social cues (Schwander, Lo, Beekman, Oldroyd, & Keller, ). However, four ant taxa have independently evolved an unusual genetic system called “social hybridogenesis,” wherein queen‐worker caste determination is primarily shaped by genetic factors (Cahan et al, ; Cahan & Vinson, ; Julian, Fewell, Gadau, Johnson, & Larrabee, ; Leniaud, Darras, Boulay, & Aron, ; Norman, Darras, Tranter, Aron, & Hughes, ; Romiguier, Fournier, Yek, & Keller, ). In these taxa, two genetic lineages coexist within populations.…”
Section: Introductionmentioning
confidence: 99%